Dendritic Spacing and Macrosegregation Affecting Microhardness of an Al-Si-Mg Alloy Solidified Under Unsteady State Conditions - Silva, Cassio da; Soares, Thiago; Cheung, Noe; Garcia, Amauri; Reis, Danieli A. P.; Brito, Crystopher [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2019)
The prediction of microstructure morphology is fundamental for the manufacture of metallic components, since the expected levels of mechanical properties will be associated with the final aspects of the microstructure. In this work, an Al-7wt.%Si-3wt.%Mg alloy was directionally solidified in unsteady state conditions in order to investigate the influence of the addition of 3wt.%Mg to an Al-7wt.%Si alloy on the solidification evolution. The microstructure of the examined alloy is shown to be characterized by a more complex arrangement of phases, as compared to that of the Al-7wt.%Si alloy, which includes the binary (alpha-Al+Mg2Si) and refined ternary (alpha-Al+Si+Mg2Si+Fe-rich IMC) eutectic mixtures. A higher Vickers hardness profile is shown to be associated with a more refined microstructural arrangement. However, for cooling rates lower than 2K/s the microhardness is shown to increase with the increase in the microstructural spacing, which is shown to occur caused by Si macrosegregation and higher content of free Mg.
Keywords: Al-Si-Mg alloys; solidification; microstructure; intermetallic compound; microhardness